Advanced stage empyemas in community-acquired pneumonia: how hospital re-organization during the Covid-19 pandemic affected the increase in surgically treated cases - Conti, Luigi; Delfanti, Rocco; Grassi, Carmine; Chiesa, Sara; Cattaneo, Gaetano Maria; Capelli, Patrizio; Banchini, Filippo (Acta Biomedica Atenei Parmensis, 2022)
The cause of pleural empyema is bacterial pneumonia and three stages has been described in the evolution of this disease: exudative, fibrino-purulent and organizational phases. The first therapeutic intervention is the antibiotic therapy; where pharmacological therapy alone is not sufficient to eradicate the infection, it is also necessary a surgical treatment. Since the province of Piacenza having been in the epicenter area during the first Sars-Cov 2 pandemic wave in March 2020 and the number of patients with Covid-related pneumonia required invasive and non-invasive respiratory support, had a considerable organizational impact on pulmonology and respiratory unit, hindering an optimal treatment of the bacterial pneumonia both in community as well as in the hospital.Among the many "collateral" damages of the epidemiological wave of the infection with Sars Cov-2, we have been able to observe in our Hospital, also an increase of pulmonary empyemas diagnosed at an advanced stage for what we believe to be organizational and social causes directly related to the pandemic: in order to cope with the emergency the Unit of Pneumology has been since March nearly uninterruptedly dedicated to the exclusive treatment of covid patients so the pneumologist has been removed due to the need from outpatient and residential management of general pneumology